Navigating the Future Husband: Perempuan Muda, Negosiasi Pernikahan dan Perubahan Sosial - Rani Dwi Putri; Prasakti Ramadhana Fahadi; Amelinda Pandu Kusumaningtyas; Ariane Utomo; Oki Rahadianto Sutopo (Jurnal Studi Pemuda, 2020)
Economic development and social-political change in Indonesia have been accompanied by wider education access especially for women. These have resulted in a number of profound inter-generational shifts in the process of transition to work and marriage – one of them is a trend toward self-choice marriage. This study uses qualitative methods in particular in-depth interviews and focus group discussion as data collection techniques. By combining two theoretical lenses of generation change and post-feminism, this article explores the practice and meaning of choices in the quest for an ideal husband, through exploring the subjective narrative of four young women. All informants have their own point of views about the ideal partner criteria, thus representing uniqueness and diversity of contemporary generation. Terms such as pious, responsible and economically-established are still considered important in their imagination, however, the most essential for an ideal partner is a prospective man who can negotiate between work role, family and tradition in the context of late modernity. It can be argued that those views are frequently influenced by existing normative values of family and neighbourhood showing that ‘feminist consciousness’ is still a privilege.